Transcending borders in higher education: Internationalisation policies in Sweden - Alexiadou Nafsika; Rönnberg Linda (Sage Publications, 2025)
This article examines the national and European policy contexts that shaped the Swedish internationalisation agenda in higher education since 2000, the policy ideas that were mobilised to promote it, and the national priorities that steered higher education debates. The analysis highlights how domestic and European policy priorities, as well as discourses around increasing global economic reach and building solidarity across the world, have produced an internationalisation strategy that is distinctly ‘national’. Drawing on the analysis of the most recent internationalisation strategies we argue that the particular Swedish approach to internationalisation has its ideational foundations in viewing higher education as a political instrument to promote social mobility and justice, as well as a means to develop economic competitiveness and employability capacity. In addition, internationalisation has been used to legitimise national reform goals, but also as a policy objective on its own with the ambition to position Sweden as a competitive knowledge nation in a global context.